Examining Consumer Decisions on Bokashi Fertilizer: Insights from P4S "Karya Tani", Bagorejo Village, Gumukmas District, Jember Regency - Kurniawati, Dewi; Sasmito, Mochammad Shandy; Muksin (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This research aims to test and analyze the influence of individual characteristics, the environment, and marketing communications on decision making to purchase production bokashi fertilizer P4S "Karya Tani" , both jointly and partially, and testing which variables have the most dominant influence on purchasing decisions. This research used a survey method with a sample size of 30 people conducted on consumers using P4S "Karya Tani" bokashi fertilizer. Overall, the results of this research can be concluded that individual characteristics, the environment, and marketing communications together have a significant influence on decision making to purchase bokashi fertilizer produced by P4S "Karya Tani". Partially, individual characteristics and marketing communications have a significant effect, while the environment has an insignificant effect. The factors that have a dominant influence on decision making to purchase P4S "Karya Tani" bokashi fertilizer are individual characteristics.